Re-evaluating the place attachment concept and developing the new place relatedness scale: evidences from Serbia - Solarević, Milica; Đerčan, Bojan; Brunn, Stanley; Bubalo-Živković, Milka; Gatarić, Dragica; Penjišević, Ivana (Geographica Pannonica, 2023)
The attachment can be directed towards the people (socially based attachment), but also can be based on the physical characteristics of the place or other factors. People in Serbia frequently change place of residence during educational stages or due to important family and life events. It also depends on other factors, such as ethnicity, tradition and environmental concerns. This study aims to re-evaluate the place attachment concept based on the well-established triple person-process-place concept and develop a new place attachment scale and apply. The survey included 1059 respondents. The SPSS was used for EFA calculations, Independent T-tests, and One-way ANOVA, while R and RStudio were used for CFA analysis. Four groups of factors were identified, leading to the development of a four-dimensional Place Relatedness Scale (4PRS): Family and Home, Social, Community and Everyday Life, Local Environment Bonding, Life Cycle. Certain differences were found between male and female respondents and in regard to other socio-demographic parameters.
Keywords: place; place attachment; place attachment scale; Serbia